“It’s the 21st century, but this is still a boy’s club” - Gender, money and power in Inventing Anna - Intveen, Julie (MEIN FACH Englisch Sek II)

The True Story Of A Total Fake. Eine Untersuchung des didaktischen Potenzials der Hochstaplerin Anna Delvey in der Miniserie Inventing Anna - Intveen, Julie (Hochstapelei in der Gegenwartskultur. Literaturwissenschaftliche und literaturdidaktische Perspektiven)
Figuren der Hochstapelei faszinieren als Meister:innen der Verstellung. Ob in Literatur, Film oder Realität – sie inszenieren sich virtuos und entlarven die Oberflächlichkeit einer Gesellschaft, die sich von Äußerlichkeiten blenden lässt. Sie stellen soziale Grenzen infrage und verkörpern einen subversiven Geist, der den Wunsch nach Ausbruch widerspiegelt. Doch was poetisch bewundert wird, ist real oft justiziabel und hat zerstörerische Folgen für die Betrogenen. Dieser Band nähert sich der Hochstapelei als kultureller Praxis der Gegenwart. Welche gesellschaftlichen, kulturellen und medialen Bedingungen begünstigen das Hochstapeln? Und was bedeutet es für die Identitätsarbeit in der Moderne, wenn die Grenzen zwischen Sein und Schein verschwimmen? Anknüpfend an bisherige Forschungsdiskussionen versammeln die literaturwissenschaftlichen und literaturdidaktischen Beiträge Antworten auf diese Fragen. Darüber hinaus beleuchten sie die enge Verknüpfung von Fiktion, Täuschung und Selbstinszenierung.

Beyond The Episode: A Case For Serial Literacy in EFL Education - Intveen, Julie; Illigens, Tim (Journal of Media Literacy Education)
Serial storytelling, characterized by its interplay of vertical (episodic) and horizontal (long-form) narrative structures, offers a unique opportunity for media literacy in English as a Foreign Language (EFL) education. This paper argues for the development of a serial literacy framework, a concept that expands traditional film literacy models to accommodate the distinct demands of serialized narratives. By using Inventing Anna (Rhimes, 2022) as a case study, the study explores how serial storytelling fosters engagement with themes of identity construction, ethical ambiguity, and transmedial storytelling. This paper elaborates on serial literacy, considering its implications within foreign language learning contexts. The study highlights how serialized narratives cultivate critical thinking, communicative competence, and media awareness, which renders them a valuable pedagogical tool. By integrating serial literacy into EFL curricula, educators can bridge students’ media consumption habits with analytical engagement and thus foster a generation of critically literate media consumers and producers. This paper elaborates on serial literacy, considering its implications within foreign language learning contexts. The study highlights how serialized narratives cultivate critical thinking, communicative competence, and media awareness, which renders them a valuable pedagogical tool. By integrating serial literacy into EFL curricula, educators can bridge students' media consumption habits with analytical engagement and thus foster a generation of critically literate media consumers and producers.

The Political Era of Taylor Swift - Exploring the influence of Miss Americana at the ballot box - Intveen, Julie; Janzen, Thomas (MEIN FACH - Englisch Sek II)

The Commonwealth Games. Hosting the games – creating pitches - Intveen, Julie (MEIN FACH - Englisch Sek II)

Commonwealth Connections. Discovering global dynamics through Model UN discourse - Intveen, Julie (MEIN FACH - Englisch Sek II)

„Tolle lege! Aber was liest man eigentlich, wenn man englische Romane deutscher Schulbuchverlage liest?“ - Intveen, Julie; Hohwiller, Peter (HeLix Dossiers zur romanischen Literaturwissenschaft)

Separation of Art & Artist? Exploring the J.K. Rowling Controversy - Intveen, Julie (MEIN FACH - Englisch Sek II)

Narratives of Deception - A Didactic Approach to Serial Literacy - Intveen, Julie

Buzzing Progress or Dangerous Path? Exploring Ethics of technology and environmentalism in "Black Mirror's" Hated in the Nation - Intveen, Julie (MEIN FACH - Englisch Sek II)

The True Story Of A Total Fake: Identitätsfragen mit der Netflix Serie Inventing Anna unterrichten - Intveen, Julie (Fernsehserielles Erzählen im fächerübergreifenden Unterricht: Forschungs- und unterrichtspraktische Perspektiven)

“I was trying to protect you. I was trying to keep you safe.” Parental surveillance in the Black Mirror episode Arkangel - Intveen, Julie (Englisch betrifft uns)

The United Kingdom: A Multicultural Society Education as a key to life in mixed communities - Intveen, Julie; Bauer, Maike (Englisch betrifft uns)

The Royal Divide - Exploring the impact of Megxit on the future of the British monarchy - Intveen, Julie; Bauer, Maike (Englisch betrifft uns)

The True Story of a Total Fake – Eine Untersuchung des didaktischen Potentials von Netflix‘ Inventing Anna - Intveen, Julie; Hohwiller, Peter (Fernsehserielles Erzählen im fächerübergreifenden Unterricht)

Fictions of Identity – A Didactic Exploration of TV Series - Intveen, Julie (15. Nachwuchstagung der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF), Thema: Findungsphasen)

Fictions of Identity – A Didactic Approach to Serial Literacy - Intveen, Julie (Media Literacy in Language (Teacher) Education)

Chasing the American Dream: Chances and challenges of immigrant families – a media task - Intveen, Julie (Englisch betrifft uns)

The United Kingdom: A Multicultural Society Education as a key to life in mixed communities - Bauer, Maike; Intveen, Julie (Englisch Betrifft Uns)

The Royal Divide - Exploring the impact of Megxit on the future of the British monarchy - Bauer, Maike; Intveen, Julie (Englisch Betrifft Uns)